Characteristics and influencing factors of metal distribution in different wetlands of the Liaohe Delta, Northeastern China - Yu, Yang; Zhang, Jiapeng; Qin, Jifa; Yang, Jisong; Wang, Zhikang; Song, Ningning; Yu, Junbao (Frontiers in Marine Science, 2022)
Metal distribution in different wetlands under the complex influence of natural and anthropogenic activities in the Liaohe Delta was analyzed to better protect and manage delta areas. Ninety-six soil samples were collected from six wetland types, and the levels, depth distributions, risk, and influencing factors of metals (i.e., As, Cd, Cr, Ni, Cu, Pb, Zn, Mn, Al, and Fe) were analyzed. The results showed that the concentrations of As, Cd, Cr, Ni, Zn, and Al in more than 70% of the soil samples were higher than the background value of Liaoning Province. The concentration of As decreased with distance from the estuary, while that of Cr was higher downstream of Liaohe. The spatial distributions of Cd, Ni, Cu, Pb, and Zn were similar. The concentrations of most metals in the topsoil were higher than those in the subsoil. According to the Nemerow pollution index, higher pollution was observed in the area far away from the Liaohe River and Bohai Sea for the topsoil layer, while for the subsoil layers, higher pollution was observed in the area near the Liaohe estuary. The correlation analysis showed that the wetland type was clearly correlated with Cd, Cu, Al, and S. The concentrations of Cd, Pb, Zn, C, N, P, and S and the electrical conductivity obviously decreased with soil depth, while the concentration of Mn was positively correlated with soil depth. Mn was negatively correlated with total organic carbon (TOC), total nitrogen (TN), and total phosphorus (TP), whereas Cd, Pb, and Zn showed positive correlation with TOC, TN, and total sulfur (TS). The general linear model indicated that wetland type had a significant effect on As, Cd, Ni, Cu, Pb, Zn, Al, and Fe (p< 0.01), while depth had a significant effect on Cd, Cr, and Pb (p< 0.01). The findings of this work will contribute to pollution control and ecosystem health conservation of the Liaohe Delta.